Practice of Textbook Adaptation in English Language Classrooms: Insights from Secondary Level Teachers (SNPRC Journal, 2025)
Textbook adaptation plays a pivotal role in the EFL classroom as a single textbook cannot meet the diverse needs, levels and cultural heritage of all the students. The present study aims to explore the practice of textbook adaptation employed by secondary level EFL teachers in Nepal. To accomplish the objective, the data were purposively collected from the five EFL teachers of Rupandehi district using semi-structured interviews.The study concludes that textbook adaptation is one of the challenging jobs of teachers, which is usually guided by teachers’ beliefs, classroom contexts and institutional pressures. Teachers state that a single textbook cannot meet the diverse needs, and levels of the students. Some teachers make use of textbooks for helping examinations, while others use it making class more engaging and lively. Strategies, such as omission, addition, modification, and reordering are used in adapting process. The factors, such as exam-oriented curricula, institutional pressure, limited time and resource hinder the adaptation process. Similarly, experienced teachers are more flexible in textbook adaptation than novice teachers. Despite these limitations, adapting textbook help the teachers to minimize the gaps between prescribed materials and contextual needs. The findings suggest that teachers should enhance their adaptation skills and their institutions should support them with resources and time.